Phyllanthus emblica: a comprehensive review of its phytochemical composition and pharmacological properties - Prananda, Arya Tjipta; Dalimunthe, Aminah; Harahap, Urip; Simanjuntak, Yogi; Peronika, Epina; Karosekali, Natasya Elsa; Hasibuan, Poppy Anjelisa Zaitun; Syahputra, Rony Abdi; Situmorang, Putri Cahaya; Nurkolis, Fahrul (Frontiers in Pharmacology, 2023)
Phyllanthus emblica Linn, a prominent member of the euphorbiaceae family, exhibits extensive distribution across a multitude of tropical and subtropical nations. Referred to as "Balakka" in Indonesia, this plant assumes various names across regions, such as "kimalaka," "balakka," "metengo," "malaka," and "kemloko" in North Sumatra, Ternate, Sundanese, and Java respectively. Phyllanthus emblica thrives in tropical locales like Indonesia, Malaysia, and Thailand, while also making its presence felt in subtropical regions like India, China, Uzbekistan, and Sri Lanka. The fruits of Balakka are enriched with bioactive constituents recognized for their wide-ranging benefits, including antioxidant, anti-aging, anti-cholesterol, anti-diabetic, immunomodulatory, antipyretic, analgesic, anti-inflammatory, chemoprotective, hepatoprotective, cardioprotective, antimutagenic, and antimicrobial properties. Comprising a spectrum of phenolic compounds (such as tannins, phenolic acids, and flavonoids), alkaloids, phytosterols, terpenoids, organic acids, amino acids, and vitamins, the bioactive components of Malacca fruit offer a diverse array of health-promoting attributes. In light of these insights, this review aims to comprehensively examine the pharmacological activities associated with Phyllanthus emblica and delve into the intricate composition of its phytochemical constituents.